Ginsenoside-Rb1 Promotes Adipogenesis Through Regulation of PPARγ and MicroRNA-27b - Chan, L.-S.; Yue, P. Y.-K.; Kok, T.-W.; Keung, M.-H.; Mak, N.-K.; Wong, R. N.-S. (Hormone and Metabolic Research, 2012)
Ginsenoside-Rb1 (Rb1), one of the bioactive components in ginseng extract, is recently reported to be able to promote adipogenesis and peroxisome proliferator-activated receptor gamma (PPARγ) expression. Meanwhile, microRNA-27b (miR-27b) is also identified to regulate adipogenesis by targeting PPARγ2. In the present study, we attempted to link up the Rb1-promoted adipogenesis with PPARγ binding and miR-27b regulation. First, we demonstrated that GW9662, an antagonist of PPARγ, could block Rb1-induced 3T3-L1 differentiation with little toxicity towards cell proliferation. Then, expression levels for both of miR-27b and its primary transcript, pri-mir-27b, were found to decrease upon Rb1 treatment. Again, GW9662 could attenuate the inhibitory effect of Rb1 on both miR-27 and pri-mir-27b expression. Since Rb1 was demonstrated to have binding activity towards PPARγ, we thus speculate that Rb1 may act though PPARγ to downregulate mir-27b gene transcription and mature miR-27b activity, which in turn promotes PPARγ expression and adipogenesis. Enhancement on adipogenesis of adipose tissues is expected to prevent lipotoxicty in nonadipose tissues. Our data may give a better illustration to explain the antidiabetic effect of Rb1 and provide a hint on treatment of lipid related metabolic diseases in the future.
Keywords: ginsensoside-Rb1; PPARγ; adipogenesis; miR-27b; 3T3-L1 adipocytes